Efficacy of Online Training of the Elected Representatives of Local Rural Government: A Focus Group Study - Mukherjee, Debarshi; Chakraborty, Subhayan; Jena, Lokesh Kumar; Hasan, Khandakar Kamrul; Debnath, Ranjit; Mitra, Sudakshina (Journal of Education Culture and Society, 2023)
Aim. Before COVID-19, training institutions rarely used eLearning to improve Elected Representatives' (ERs) skills in rural development who come from vernacular social and academic backgrounds. Online education has numerous upsides, but there is always some controversy about whether or not every learner will benefit from the same approach. The study was conducted in Tripura, a North-Eastern state of India, examine the efficacy of online training among the ERs responsible for extending the rural local government services to the common people.Methods. This study utilised the qualitative technique of focus group discussion to acquire a comprehensive grasp of the positive and negative opinions of ERs regarding their experiences with online training. Samples were collected from all the districts and all three tiers of rural government.Results. The study is a pioneering work to evaluate views of ERs on e-learning. Lack of technical support, boredom in training sessions, and lack of allowances for internet use, transportation to headquarters for training, and refreshments contributed the trainees' negative experiences. Further, training materials were poorly presented and failed to convey the intended message.Conclusions. This study will enable trainers, administrators, and policymakers to reengineer their andragogic structures of future grassroots online training programmes for higher efficacy. ERs dislike e-learning, and government regulations that favour classroom instruction worsen this issue. Policy initiatives to reconcile demand and supply, such as high-quality capacity building for Rural Local Bodies (RLBs) ERs with vernacular academics, are needed to achieve practical results.